Sadness In Human Life: A Study From The Qur'Anic Perspective - Abas, Nur Afifah (2024)
Struggling to regulate sadness is a major risk factor for developing depression from sadness dysregulation (malfunction). However, depression is potentially prevented with effective cognitive emotion regulation from the normal sadness stage. One of the ways is to educate patients overcoming negative religious coping, e.g., most depressed Muslim patients complained that they believe "being sad is sinful/immoral", which interferes with regulating sadness. Recently, this problem can be overcome by intervening cognitive reappraisal psychospiritually. Therefore, this study aims to propose add-ons to the Metacognitive Training for Depression. It has three main objectives: (1) to counteract the stigmatising misperception (2) to produce simple therapy from the Qur'anic verses (3) to construct cognitive narration about 'Sadness in Human Life' for making sense process. Methodologically, it was applying Qur'anic Reflexive Thematic Analysis, which is a novel analytical procedure using NVivo (a qualitative data analysis software). The research findings are, respectively: (1) Islam recognises the inborn sadness, but it is divided into praiseworthy and blameworthy categories according to the Divine Guidance; (2) a set of Qur'anic self-statements to reappraise cognitively (3) a cognitive narration to make sense about "Sadness in Human Life" narrative. It is a potentially effective content for primary health care professionals to communicate with religious Muslim outpatients/inpatients who complain about sadness regulation difficulty. Ideally, Muslims must be similarly trained from childhood to gradually enhance their resilience against saddening life tests.